Circulating Apoptotic Signals During Acute and Chronic Exposure to High Altitude in Kyrgyz Population - Kosanovic, Djuro; Platzek, Simon Maximilian; Petrovic, Aleksandar; Sydykov, Akylbek; Maripov, Abdirashit; Mamazhakypov, Argen; Sartmyrzaeva, Meerim; Muratali Uulu, Kubatbek; Cholponbaeva, Meerim; Toktosunova, Aidana; Omurzakova, Nazgul; Duishobaev, Melis; et al. (Frontiers in Physiology, 2019)
Background. Circulating apoptotic signals (CAS) have been described in the pathologies associated with dysregulated apoptosis, such as cancer, heart diseases and pulmonary hypertension (PH). However, nothing is known about the expression profiles of these markers in the circulation of humans exposed to acute and chronic effects of high altitude (HA). Methods. Gene expression levels of different apoptotic signals (AS) were analyzed in human pulmonary artery smooth muscle cells (PASMCs) upon hypoxia incubation. In addition, we measured the plasma values of relevant CAS in Kyrgyz volunteers during acute and chronic exposure to HA. Finally, we analyzed the effects of pro-apoptotic mediator Fas ligand (FasL) on apoptosis and proliferation of human PASMCs. Results. Several cellular AS were increased in PASMCs exposed to hypoxia, in comparison to normoxia condition. Among analyzed CAS, there was a prominent reduction of FasL in lowlanders exposed to HA environment. Furthermore, decreased circulatory levels of FasL were found in highlanders with HA-induced PH (HAPH), as compared to the lowland controls. Furthermore, FasL concentration in plasma negatively correlated with tricuspid regurgitant gradient values. Finally, FasL exerted pro-apoptotic and anti-proliferative effects on PASMCs. Conclusion. Our data demonstrated that circulating levels of FasL are reduced during acute and chronic exposure to HA environment. In addition, dysregulated FasL may play a role in the context of HAPH due to its relevant functions on apoptosis and proliferation of PASMCs.